Faktor yang Berhubungan Dengan Rendahnya Penggunaan KB Implant Pada Wanita Pasangan Usia Subur (WUS) di Desa Pintupadang Kecamatan Batang Angkola Tahun 2020 - Daulay, Suryani Agustina (Jurnal Kesehatan Ilmiah Aufa Royhan, 2020)
Family planning program is an effective way to prevent maternal and child mortality because it can help married couples avoid high-risk pregnancies, reduce the risk of maternal mortality through pregnancy prevention, delay, gestational age and spacing pregnancies with the main target being couples of reproductive age . The purpose of this study was to determine the factors associated with the low use of implant family planning in women with fertile age couples (WUS) in Pintupadang Village, Batang Angkola District in 2020. This study used an analytical survey with a cross sectional approach. The population used was all women in fertile age (WUS) in the village of Pintupadang, Batang Angkola District, amounting to 40 people. Sampling was carried out using the total population technique. This research was conducted in Pintupadang Village, Batang Angkola District. Data analysis using the Chi-Square test. The results of this study were knowledge with a value of p = 0.001 (<0.05), parity with a value of p = 0.013 (<0.05) and husband's support with a value of p = 0.005 (<0.05). The conclusion of this study is that there are factors that are associated with the low use of implant planning in women with fertile age couples (WUS) in Pintupadang Village, Batang Angkola District in 2020.